A MULTICENTRIC STUDY ON BREAST CANCER IN ULTRA YOUNG WOMEN: I – A CLINICAL AND EPIDEMIOLOGIC PICTURE - Yoshimura, Adriana Akemi; Mattar, André; Mota, Bruna S.; Fristachi, Carlos Elias; Pessoa, Eduardo Carvalho; Andrade, Felipe Eduardo; Tosello, Giuliano; Vespoli, Heloísa Maria De Luca; Oliveira Junior, Idam de; Borges, João Bosco Ramos; Filassi, José Roberto; Gebrim, Luiz Henrique; et al. (Mastology, 2021)
Introduction: A substantial number of young women (YW) is affected by breast cancer (BC), an important cause of death in young age. The definition of a YW in a BC context varies in the literature. Considering specific characteristics, such as reproductive factors and hereditary risk, we defined ultra young women (UYW) as women aged 30 years or less. Despite the fact that specialized centers are increasingly providing assistance to UYW with BC, important aspects of the disease in this age remain controversial. Objective: Evaluate clinical and epidemiological characteristics of BC in UYW in the State of São Paulo. Methods: We conducted a multicentric, observational, retrospective study of consecutive BC in UYW patients in nine Services. Only patients with infiltrating BC aged 30 years or less were included. The following data were collected: age, body mass index, parity, hormonal contraception use, history of breast/ovarian cancer in the family, path- ological tumor category and clinical staging. Frequency parameters were estimated. The research protocol was approved by the Ethics Committee of all collaborative centers. An informed consent was waived. Results: The study population included 293 patients. Age varied between 19 and 30 years (mean 27.3; median 28). Considering body weight, we found that 37.1% of the patients were overweight or obese. 58.6% were current or past HC users. Nulliparity was referred in 44.4%. 246 cases reported family history of BC which was verified in first degree relatives in 37.9%, while 66 patients referred BC in any member of the family. Only 33 patients went through a multigene testing panel: pathogenic inherited variants were detected in 37.5%. Remarkably, locally advanced tumors were diagnosed in 57.1%. Tumor sizes at diagnosis were: T1-11.8%, T2-33.8%, T3-31.6% T4-19.9% and T4d-2.9%. Clinical axillary lymph nodes evaluation revealed: N0-35%, N1-42.8%, N2-18.7%, and N3-3.5%. Systemic metastases at diagnosis were observed in 29 cases, that were classified as stage IV “de novo” (9.8%). The metastases sites were multiple in 31% and the clinical staging in the diagnosis are later. Conclusion:An unfavorable picture was observed in UYW with BC. We found a high rate of advanced neoplasias, with adverse clinical prognostic factors. To change the present-day scenario, we need to educate the population, enhancing BC awareness and self-body attention since adolescence, besides stimulating the adoption of a healthy lifestyle.